Questioning the inclusivity of events: the queer perspective. Issue 11 (2nd December 2021) - Ong, Faith; Lewis, Clifford; Vorobjovas-Pinta, Oscar
Abstract: Event programmes are typically designed with a target audience in mind, and such design can inherently signal inclusion or exclusion of marginalised segments. This is particularly the case for lesbian, gay, bisexual, transgender, intersex and queer (LGBTIQ+) individuals, whose sexual and gender identities position them as an invisible minority on the periphery of society. Given the role of events in building community spirit, it is essential to ensure all members of a community feel able to participate in order to create a sense of belonging, fulfilling Sustainable Development Goals of inclusivity in community. Through the lens of Social Dominance Theory and in pursuit of equality for LGBTIQ+ communities, in-depth interviews were conducted with sexually diverse (queer) participants to explore their perceptions of inclusivity at community events. This study explored how elements of an event could serve to enhance or attenuate prejudice, and therefore influence the inclusion of LGBTIQ+ communities.